MicroRNA-132 provides neuroprotection for tauopathies via multiple signaling pathways - El Fatimy, Rachid (Acta Neuropathol, 2018)
MicroRNAs (miRNA) regulate fundamental biological processes, including neuronal plasticity, stress response, and survival. Here, we describe a neuroprotective function of miR-132, the miRNA most significantly downregulated in neurons in Alzheimer’s disease. We demonstrate that miR-132 protects primary mouse and human wild-type neurons and more vulnerable Tau-mutant neurons against amyloid β-peptide (Aβ) and glutamate excitotoxicity. It lowers the levels of total, phosphorylated, acetylated, and cleaved forms of Tau implicated in tauopathies, promotes neurite elongation and branching, and reduces neuronal death. Similarly, miR-132 attenuates PHF-Tau pathology and neurodegeneration, and enhances long-term potentiation in the P301S Tau transgenic mice. The neuroprotective effects are mediated by direct regulation of the Tau modifiers acetyltransferase EP300, kinase GSK3β, RNA-binding protein Rbfox1, and proteases Calpain 2 and Caspases 3/7. These data suggest miR-132 as a master regulator of neuronal health and indicate that miR-132 supplementation could be of therapeutic benefit for the treatment of Tau-associated neurodegenerative disorders. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s00401-018-1880-5) contains supplementary material, which is available to authorized users.